Conjunctival Pyogenic Granuloma after Strabismus Surgery - Shinji Makino; Kozue Hozawa (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2014)
A 48-year-old man presented with exotropia of his left eye. The alternative prism cover test demonstrated there was 60 prism diopter exotropia. A 9 mm lateral rectus muscle recession and a 7 mm medial rectus muscle resection were performed in his left eye. Approximately one month later, a polypoid, red, smooth-surfaced mass arose from the area overlying the original insertion of lateral rectus muscle (Figure 1A). We diagnosed this mass as pyogenic granuloma. One month after administration with topical corticosteroid drops, this mass was completely resolved (Figure 1B). There was no recurrence during the 2 years after surgery.